2019
DOI: 10.2196/13245
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the Use of Mobile Apps During the Treatment of Breast Cancer: Systematic Review

Abstract: Background Cancer is a major cause of morbidity, disability, and mortality worldwide, and breast cancer is the most common cause of death in women. Different modalities of cancer treatment can have adverse effects that reduce the quality of life of patients and lead to treatment interruptions, if not managed properly. The use of mobile technologies has brought innovative possibilities for improving health care. Mobile apps can help individuals manage their own health and well-being and may also pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 24 publications
1
36
0
2
Order By: Relevance
“…Although there are a number of well-researched, psychometrically sound and widely used measures for monitoring the symptom burden, psychosocial needs and quality of life of patients with cancer, additional work is needed [51,52]. This work could take advantage of available and emerging technologies, such as the use of mobile devices to detect problems at relevant points in time, and eHealth interventions that make psychosocial interventions more accessible to a larger number of patients at lower costs.…”
Section: Psychosocial Oncology Researchmentioning
confidence: 99%
“…Although there are a number of well-researched, psychometrically sound and widely used measures for monitoring the symptom burden, psychosocial needs and quality of life of patients with cancer, additional work is needed [51,52]. This work could take advantage of available and emerging technologies, such as the use of mobile devices to detect problems at relevant points in time, and eHealth interventions that make psychosocial interventions more accessible to a larger number of patients at lower costs.…”
Section: Psychosocial Oncology Researchmentioning
confidence: 99%
“…Ginossar et al [ 34 ] performed a systematic review of literature and found over 100 breast cancer-related mobile apps; however, many of them did not lead to behavior change and many were not evidence-based. Recent mobile apps for women with breast cancer have a positive effect by promoting weight loss, decreasing stress, and improving the quality of life [ 35 , 36 ]. Apps for reporting symptoms and promoting self-care during cancer chemotherapy treatment are still rare [ 6 - 11 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this viewpoint, mobile health (mHealth) apps in cancer care have emerged as an attractive technology for enabling symptom and disease management and promoting healthy lifestyles such as increasing physical activity [9][10][11][12][13]. An increasing number of mHealth apps for patients with breast cancer are being developed; these apps aid in establishing an association between patients and health care professionals [9,[14][15][16]. Currently, approximately 600 mobile apps for patients with breast cancer are available in the iOS and Android markets [16].…”
Section: Introductionmentioning
confidence: 99%